Impacts of the COVID-19 pandemic on treatment-seeking college students - Natalie R. Pottschmidt; Rebecca A. Janis; Brett E. Scofield; Alaina L. Cummins; Dever M. Carney; Katherine A. Davis; J. Ryan Kilcullen; Hongjun (Michael) Tan; Louis G. Castonguay; Benjamin D. Locke (Cogent Mental Health)
While the impact of the coronavirus disease (COVID-19) pandemic has been ubiquitous and pervasive, there is still little known about how specific groups may be impacted differently. Epidemiological survey research suggests that college students are at heightened risk for negative mental health effects of the pandemic, but most research on collegiate mental health during the pandemic has been focused on the general student body and limited in scope. The current research presents two studies examining impacts of COVID-19 in a large clinical sample of treatment-seeking college students, using data collected through the Center for Collegiate Mental Health. First, examining baseline psychological symptom distress in a pre-COVID and a COVID cohort, few differences were seen between the two groups. Second, for students seeking counseling after COVID-19 onset, reported negative impacts of the pandemic across life areas are presented, along with their associations with psychological symptoms, demographics, and reasons for seeking treatment. Students who reported a negative impact of COVID-19 on their mental health were more likely to present with increased baseline symptom distress. Furthermore, students with minoritized identities were often disproportionately negatively impacted across life areas assessed. Recommendations for clinicians, counseling centers, and institutions are highlighted based on this examination.